Introducing APEL - Challis, Maggie, 1952- (Further education (London, England), 1993)
The fact that learning accumulates and exists outside an education or training environment cannot be disputed. Yet traditionally, it is only institutional, certificated learning that carries any status. Accreditation of Prior Experiential Learning systems seek to give positive credit for all learning, by placing it within a recognized accreditation framework. In the light of recent legislation, APEL systems offer the key towards more flexible and open delivery systems for further education. Maggie Challis offers a detailed, practical introduction to the skills and processes of implementing an A.